EFEKTIVITAS METODE COMMUNITY LANGUAGE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB SISWA KELAS V MI IKHLASIYAH PALEMBANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effectiveness of the Community Language Learning (CLL) method in improving Arabic language learning outcomes for fifth-grade students at MI Ikhlasiyah Palembang. The problem identified in this research stems from observations indicating that most students consistently scored below the Minimum Competency Criteria (KKM = 65), due to the predominance of rote-memorization-based instruction. This study aims to describe students' Arabic learning outcomes before and after the implementation of the CLL method, as well as to determine the significance of its effectiveness. A quantitative approach with a quasi-experimental design (pretest-posttest control group) was employed, involving 24 students in the control class and 26 in the experimental class. Data were collected through written tests and analyzed using normality (Shapiro-Wilk), homogeneity (Levene's Test), and hypothesis testing (Independent Sample T-Test). The results show that the experimental class's mean score increased from 37.8 (pretest) to 83.4 (posttest), with a gain of 45.6 points, and 100% of students achieved the KKM. The control class improved from 39.8 to 66.6 with a gain of 26.8 points, and only 54.2% achieved the KKM. The T-test yielded t = -3.633 with Sig. (Two-Sided p) < 0.001, indicating that the CLL method significantly and effectively improved Arabic language learning outcomes at MI Ikhlasiyah Palembang.